The Role Of Dividend Policy In Mediating The Relationship Of Profitability To Firm Value: Empirical Study On The Business Index-27 On The Indonesian Stock Exchange - Kiki Liya Fitriani; Akhmadi Akhmadi; Wawan Ichwanudin (Institute of Advanced Knowledge and Science, 2025)
This study was conducted to determine the effect of dividend policy in mediating the relationship between profitability and firm value on the business-27 index for the 2018-2022 period. This study used a sample of 17 companies using purposive sampling method. The data used is secondary data obtained from financial reports and annual reports published on the official website of the Indonesia Stock Exchange (www.idx.co.id) and the official website of each company. The data analysis technique used is multivariate regression, partial hypothesis test and mediation test and data processing is done with the STATA version 17 statistical application. The results showed that profitability has a significant positive effect on firm value. Profitability has a significant positive effect on dividend policy. Dividend policy is able to mediate the relationship between profitability and firm value.